Bioclimatic Architecture in University Buildings: A Systematic Literature Review - Santos, Nicoly Gonçalves da Silveira; Di Trapano, Patrizia; Vasconcellos, Virgínia Maria Nogueira de (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze how bioclimatic architecture has been applied in university buildings through a Systematic Literature Review (SLR), considering the relevance of this type of facility as spaces of permanence and value formation, as well as their contribution to addressing the challenges of climate change.Methodology –  The study was structured based on an SLR protocol that included the definition of the guiding question, the selection of databases (Scopus, Web of Science, SciELO, and CAPES Journals), the inclusion and exclusion criteria, and the qualitative-quantitative analysis of the selected studies.Originality/Relevance – In a context of growing concern about the effects of climate change on human health and well-being, this work contributes to the debate by highlighting the importance of design strategies to enhance climate resilience in academic spaces, fostering healthier and more sustainable environments.Results – It was found that bioclimatic architecture is generally addressed in a functional way, with emphasis on thermal comfort, energy efficiency, and adaptation to climatic conditions, with recurrent references to sustainable retrofit, computational simulations, environmental certifications, and passive strategies.Theoretical/Methodological Contributions – The study reinforces the relevance of using SLR as a tool to systematize existing knowledge and to highlight trends, recurring methodologies, and research gaps related to bioclimatic architecture in universities, while integrating dimensions of health, climate resilience, and sustainability.Social and Environmental Contributions – The findings indicate the need to incorporate bioclimatic solutions in university projects, enhancing energy efficiency, built environment quality, and the promotion of users’ health and well-being, while strengthening the socio-environmental resilience of higher education institutions.
Keywords: Bioclimatic Architecture; University Buildings; Systematic Literature Review (SLR).